1984
DOI: 10.1177/154193128402800418
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Helicopter Flight Skills: Is there a “Critical Period” for Proficiency Loss?

Abstract: This paper presents and discusses data on the proficiency loss of Army helicopter pilots following no-flying periods of one year or longer. On two separate occasions, a group of 24 Army Individual Ready Reserve (IRR) aviators were retrained on each of 37 contact flying tasks in the UH-1 helicopter. The first retraining occurred shortly after the aviators joined the IRR Aviator Training Program. At that time, the aviators had not engaged in active-duty flying for periods ranging from 2 to 12 years; the median d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…As the aim of the current experiment was to model the decay curve of skill-based human operator control behavior, it was expected that skill decay could be captured by a positively accelerating decay curve, with fairly little skill loss right after training and a higher rate of decay later on (hypothesis 3). Such a decay curve was found in previous experiments with flying tasks comparable to the current tracking task [67,68]. The first RT of each of the groups showed that all groups exhibited significantly degraded tracking performance compared to the end of training in both pitch and roll.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As the aim of the current experiment was to model the decay curve of skill-based human operator control behavior, it was expected that skill decay could be captured by a positively accelerating decay curve, with fairly little skill loss right after training and a higher rate of decay later on (hypothesis 3). Such a decay curve was found in previous experiments with flying tasks comparable to the current tracking task [67,68]. The first RT of each of the groups showed that all groups exhibited significantly degraded tracking performance compared to the end of training in both pitch and roll.…”
Section: Discussionsupporting
confidence: 83%
“…When comparing the retention results of the three groups, it was hypothesized that skill decay can be captured by a positively accelerating decay curve, meaning that at first, skills are retained fairly well, but at some point start to deteriorate at an increasing rate (hypothesis 3). This skill-decay trend has been found in two flying task experiments [67,68] that are most comparable to the control task used in the current research.…”
Section: J Hypothesessupporting
confidence: 79%